2006
DOI: 10.1038/nm1412
|View full text |Cite
|
Sign up to set email alerts
|

Genetic model of selective COX2 inhibition reveals novel heterodimer signaling

Abstract: Selective inhibitors of cyclooxygenase-2 (COX2) have attracted widespread media attention because of evidence of an elevated risk of cardiovascular complications in placebo-controlled trials, resulting in the market withdrawal of some members of this class. These drugs block the cyclooxygenase activity of prostaglandin H synthase-2 (PGHS2), but do not affect the associated peroxidase function. They were developed with the rationale of conserving the anti-inflammatory and analgesic actions of traditional nonste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 29 publications
3
75
0
Order By: Relevance
“…For example, electrons can be transferred from a human myoglobin molecule to a tyrosyl radical in another nearby molecule (80). Funk and coworkers (58) have suggested that a PGHS-2 lacking COX activity but having POX activity may dimerize with an active PGHS-1 monomer to stimulate PGHS-1 COX activity. Our present work indicates that there is no electron transfer between the two monomers of PGHS-2 dimers leading to COX activation in a case where one of the monomers lacks POX activity and the other lacks COX activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, electrons can be transferred from a human myoglobin molecule to a tyrosyl radical in another nearby molecule (80). Funk and coworkers (58) have suggested that a PGHS-2 lacking COX activity but having POX activity may dimerize with an active PGHS-1 monomer to stimulate PGHS-1 COX activity. Our present work indicates that there is no electron transfer between the two monomers of PGHS-2 dimers leading to COX activation in a case where one of the monomers lacks POX activity and the other lacks COX activity.…”
Section: Discussionmentioning
confidence: 99%
“…Related to this, it has been proposed that PGHS-1/PGHS-2 heterodimers can form in vivo and in vitro and that the POX activity of the PGHS-2 subunit can activate the COX activity of the partner PGHS-1 subunit (58). To test for cross-talk between the POX and COX active sites of PGHS-2, we constructed, expressed, and purified a FLAGtagged G533A-/His 6 -tagged Q203R-huPGHS-2 heterodimer; the purification involved using sequential Ni-NTA and anti-FLAG affinity chromatography as described previously for COX active site mutants (32).…”
Section: Ovpghs-1 Lag Time Activitymentioning
confidence: 99%
“…Pathology-Gene knock-out studies revealed that COX-1 disruption does not yield overt kidney defects under normal conditions (5), whereas COX-2-deficient mice display postnatal renal developmental abnormalities (10,11,19). Consistent with nephron hypoplasia, nephropathy in adult COX-2 null mice (Ͼ6 weeks old) with mild to marked severity was characterized by abnormal renal cortex composed of small immature glomeruli and tubules that progressively deteriorated with increasing age (6 month age, Fig.…”
Section: Effects Of Cox-1 Knock-in On Renalmentioning
confidence: 99%
“…Isolation of Macrophages and Assay for COX Activity-Peritoneal macrophage isolation and PGE 2 generation in vitro have been reported previously (7,19). Briefly, cold sterile phosphatebuffered saline (5 ml) was injected into the peritoneal cavity, and macrophages were harvested and seeded into 60-mm dishes at 1-2.5 ϫ 10 7 cells in RPMI 1640 medium supplemented with 3% fetal bovine serum and a 1% mixture of penicillin/streptomycin solution.…”
Section: Flox-neomentioning
confidence: 99%
“…Transgenic mice are widely accepted and used in many labs. To delve the roles of prostaglandin H synthase-1 and prostaglandin H-synthase-2, known colloquially as COX-1 (target of aspirin: first level heart disease prevention drug) and COX-2 (target of many antiinflammatory drugs), in cardiovascular systems, Four different strains of mice were successfully generated and characterized including: (i) genetic knockdown of COX-1 (80-97% reduction) (Yu et al, 2005); (ii) genetic knockdown of COX-2 (80-95 % reduction) (Seta et al, 2009); (iii) knock-in of a point mutation at the COX-2 active site to abolish cyclooxygenase activity and leave peroxidase activity intact Ptgs2Y385F (Yu et al, 2006); and (iv) exchange of COX-1 into the COX-2 locus (Yu et al, 2007a). But before we head to set up more transgenic knock-in and/or knock-out mice, we should keep our own brain cool to think over the necessity and specific characters in each animal model.…”
Section: Transgenic Animal Models For Cardiovascular Diseasesmentioning
confidence: 99%